Programming 16-bit PIC microcontrollers in C : learning to fly the PIC 24 - Di Jasio, Lucio (Embedded technology series., 2007)
A Microchip insider tells all on the newest, most powerful PICs ever! FREE CD-ROM includes source code in C, the Microchip C30 compiler, and MPLAB SIM software Includes handy checklists to help readers perform the most common programming and debugging tasks The new 16-bit PIC24 chip provides embedded programmers with more speed, more memory, and more peripherals than ever before, creating the potential for more powerful cutting-edge PIC designs. This book teaches readers everything they need to know about these chips: how to program them, how to test them, and how to debug them, in order to take full advantage of the capabilities of the new PIC24 microcontroller architecture. Author Lucio Di Jasio, a PIC expert at Microchip, offers unique insight into this revolutionary technology, guiding the reader step-by-step from 16-bit architecture basics, through even the most sophisticated programming scenarios. This books common-sense, practical, hands-on approach begins simply and builds up to more challenging exercises, using proven C programming techniques. Experienced PIC users and newcomers to the field alike will benefit from the texts many thorough examples, which demonstrate how to nimbly side-step common obstacles, solve real-world design problems efficiently, and optimize code for all the new PIC24 features. You will learn about: basic timing and I/O operations, multitasking using the PIC24 interrupts, all the new hardware peripherals how to control LCD displays, generating audio and video signals, accessing mass-storage media, how to share files on a mass-storage device with a PC, experimenting with the Explorer 16 demo board, debugging methods with MPLAB-SIM and ICD2 tools, and more! A Microchip insider tells all on the newest, most powerful PICs ever! Condenses typical introductory "fluff" focusing instead on examples and exercises that show how to solve common, real-world design problems quickly Includes handy checklists to help readers perform the most common programming and debugging tasks FREE CD-ROM includes source code in C, the Microchip C30 compiler, and MPLAB SIM software, so that readers gain practical, hands-on programming experience